Singular perturbation analysis of discrete-time output feedback sliding mode control with disturbance attenuation - Nguyen, T.; Wu-Chung Su; Gajic, Z. (2009 American Control Conference, 2009)
We address the output feedback sliding mode control problem for a sampled data linear system with disturbances. By taking into account the disturbance compensation, a deadbeat high gain output feedback control strategy with additional dynamics is able to attenuate the disturbances. It is shown that the closed loop system exhibits both singularly perturbed and weakly coupled characteristics. A numerical example of an aircraft attitude output feedback control is provided to demonstrate the effectiveness of the proposed approach.